-2(4x-3)=-8x+2

Simple and best practice solution for -2(4x-3)=-8x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(4x-3)=-8x+2 equation:



-2(4x-3)=-8x+2
We move all terms to the left:
-2(4x-3)-(-8x+2)=0
We multiply parentheses
-8x-(-8x+2)+6=0
We get rid of parentheses
-8x+8x-2+6=0
We add all the numbers together, and all the variables
4!=0
There is no solution for this equation

See similar equations:

| 1200x+1.10x=2.50x | | 168g-12=0.60 | | k/3=-9=12 | | 2+10+2x=30+6+1x | | 3/n=48 | | |4x+3|=|3x+4| | | 2w/87+10w-21=180 | | 2c-16=2c-8 | | 4x-18=9(x-2)+5x | | 5x-11x-9=0 | | 10x-20=11x | | -8y+16=29 | | X²=600m² | | 1+2x=3× | | 2+2(4u-4)=-2(2u-5)+2u | | 7t+3(13/15-t)=4 | | -3(1+6r)=14- | | 34=w/2+11 | | 3(y-7)-1=-6(-4y+6)-5y | | -2(9v-9)+4v=4(v+8) | | -2(9v-9)+4v=4(v+80 | | (2x+1)/3+(x-1)/4=12/3 | | -12n-48=-6(2n+8) | | (2x+1)/3+(x-1)/4=13/2 | | 3(w-1)=2w+3-4(-4w-3) | | 5+2(4y-4)=-3(5y-3)+7y | | 4=-12y²-15y | | 2y-y=24 | | -4(-6y+5)-y=5(y-2)-4 | | 10.9k+2.56=10.7k | | 1-(6h+7)+8=-19 | | 19+8p=7p |

Equations solver categories